PENINGKATAN KETERAMPILAN BERBICARA SISWA DENGAN MEDIA GAMBAR DI KELAS II SDN 02 KAMPUNG DALAM - Marlina, Nofriza; Abidin, Zainal; Mahyuddin, Ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to describe the improvement of student’ speaking skills by using the image media in the classroom 2 SDN 02 inner village. The subjects of the study were 2 graders, amounting to 20 people. The result of the assessment of cycle I rrp obtained an average of 77 % and cycle 2 on average 100%. assesment of teacher cycle 1 aspect is average 78,7% and cycle 2 is average 92%. Grading student aspect 1 cycle average 73,7% and cycle 2, 90%. Learning outcome cycle 1, 74,9% and increase in cycle 2, 82,8%.In short the speaking skill can improve by using the image media in primary school.Keyword : Skills Improvement, Speaking, Picture Media.